MAKNA DAN NILAI BUDAYA DALAM LAGU-LAGU DAERAH MUNA SEBAGAI MODEL PEMBENTUK KARAKTER UNGGUL - Rasiah; Ansor Putra; Fina Amalia Masri; Ela Martisa; La Bilu (Universitas Hasanuddin, 2022)
Character building has become one of the government's program priorities through the mental revolution movement. The goal is to create a new mentality for the nation that is more productive, competitive and prosperous. This study aims to reveal the meaning and cultural values ​​contained in Muna folk songs as a model for building superior characters. Nine folk songs were collected as the object of this study entitled Daesalo Nekakawasa, O'Tampo, Witeno Wuna, Kaninindo Kamokula, O'Raha, Tongkuno, Damekatahi Liwu, O'Wuna, and Dapo Angka-Angkatao. The results indicate that the meanings and cultural values ​​contained in the songs are the existence of God, the Spirit of Building the Nation, Obedience to parents words. These values ​​and meanings can then be used to form superior characters, including forming religious, nationalist, mutual cooperation, and solidarity characters.